A Continuous Red Eye: Case Report of Indirect Carotid Cavernous Fistula: Poster Presentation - Case Report - Resident - Nurul Qalbi Ramadhani; dr. Andi Muhammad Ichsan, Ph.D, Sp.M(K); Dr. dr. Yunita Mansyur, Sp.M(K), M.Kes; dr. Ashari Bahar, M.Kes, Sp.S(K); FINS; FINA (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Carotid cavernous fistula (CCF) is a type of arteriovenous shunt in the cavernous sinus. Indirect CCF symptoms are not typical that can outwit us. Ocular manifestations occur because of venous and arterial stasis around the eye and orbit. The aim of this report is to increase awareness of the existence of other causes if there is no improvement after treatment. Case Illustration : A 59-year-old male presented with prolong conjunctival hyperemia on both eyes for two months that been diagnosed and treated as conjunctivitis. The ophthalmologic examination showed dilated episcleral vessels on both eyes with no evidence of infection and inflammation, this became a suspicion about the existence of a suppression from retro orbital region. The magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) brain examination were performed anda right CCF was diagnosed. The patient was referred to interventional neurology, digital subtraction angiography (DSA) examination showed a fistula in the right cavernous sinus and embolization was conducted. Discussion : The patient categorized as spontaneous, low flow, indirect CCF Barrow type D. On this type of CCF conjunctival injection is often the most prominent feature, and patients are commonly treated for other conditions, such as conjunctivitis, before a correct diagnosis is made. Conclusion : Carotid cavernous fistula can be characterized by the insidious onset of symptoms, diagnosis is based on the angiographic examination. When a sign suggestive of orbital or cavernous sinus pathology is present, a more thorough examination is crucial. Early diagnosis and appropriate management are essential to avoid vision and life threatening complications.